Temperature Affects the Time Required to Discern the Relationship between Primary Production and Export Production in the Ocean - Edward Laws (MDPI AG, 2021)
Knowledge of the relationship between net primary production (NPP) and export production (EP) in the ocean is required to estimate how the ocean’s biological pump is likely to respond to climate change effects. Here, we show with a theoretical food web model that the relationship between NPP and EP is obscured by the following phenomena: (1) food web dynamics, which cause EP to be a weighted average of new production (NP) over a previous temperature-dependent time interval that can vary between several weeks at 25 °C to several months at 0 °C and, hence, to be much less temporally variable than NP and (2) the temperature dependence of the resiliency of the food web to perturbations, which causes the return to equilibrium to vary from roughly 50 days at 0 °C to 5–10 days at 25 °C. The implication is that the relationship between NPP and EP can be discerned at tropical and subtropical latitudes if measurements of NPP and EP are averages or climatologies over a timeframe of roughly one month. At high latitudes, however, measurements may need to be averaged over a timeframe of roughly one year because the food webs at high latitudes are very likely far from equilibrium with respect to NPP and EP much of the time, and the model can describe only the average behavior of such physically dynamic systems.